Анакреонтическая поэзия Гавриила Державина - Минеева, Е. (Літературознавчі обрії. Праці молодих учених, 2010)
The article regards the formation and the development of Derzhavin’s anacreontic poetry as «light poetry». Special attention is paid to Derzhavin’s romantic lyrics and creative work. In particular such a genre variant as love lyrics is considered in detail.